Using Biomedical Text as Data and Representation Learning for Identifying Patients with an Osteoarthritis Phenotype in the Electronic Medical Record - Christopher Meaney; Jessica Widdifield; Liisa Jaakkimainen; Michael Escobar; Frank Rudzicz; Karen Tu (International Journal of Population Data Science, 2018)
Introduction Electronic medical records (EMRs) are increasingly used in health services research. Accurate/efficient identification of a target population with a specific disease phenotype is a necessary precursor to studying the health of these individuals.